Menstrual pain - Siniša Franjić (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2019)
The initiation of menstruation, called menarche, usually happens between the ages of 12 and 15 [1]. Menstrual cycles typically continue to age 45 to 55, when menopause occurs. Many women fi nd themselves reluctant to discuss the existence and normality of menstruation. The word menstruation has been replaced by a variety of euphemisms, such as the curse, my period, my monthly, my friend, the red fl ag, or on the rag. Most women experience deviations from the average menstrual cycle during their reproductive years. As a result, it is not uncommon for women to display certain preoccupations regarding their menstrual bleeding, not only in relation to the regularity of its occurrence, but also in regard to the characteristics of the fl ow, such as volume, duration, and associated signs and symptoms. Unfortunately, society has encouraged the notion that a woman's normalcy is based on her ability to bear children. This misperception has understandably forced women to worry over the most miniscule changes in their menstrual cycles. Indeed, changes in menstruation are one of the most frequent reasons why women visit their clinician.